2017
DOI: 10.18006/2017.5(5).636.643
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Purity of Inter-Specific F1 Hybrids Involving Vigna Radiata and Vigna Umbellata

Abstract: Genetic purity test of true hybrids from controlled crosses before further generations of selfing or crossing and selection is essential for Mungbean improvement. The present study was conducted to transfer mungbean yellow mosaic (MYM) disease resistance in mungbean from ricebean and to assess the genetic purity of developed inter-specific F1 hybrids using morphological features and microsatellite markers. Inter-specific crosses were made involving two genotypes of mungbean viz., K 851 and TM 96-2 and one geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…VR0200. Bhanu et al (2017) also confirmed the hybridity of V. radiata × V. umbellata interspecific hybrids using morphological and adzukibean specific SSR markers. Abbas et al (2015) used SSR and RAPD markers to confirm the hybridity of interspecific hybrids between moongbean and urdbean.…”
Section: Confirmation Of Hybridity Of Interspecific Hybridssupporting
confidence: 67%
“…VR0200. Bhanu et al (2017) also confirmed the hybridity of V. radiata × V. umbellata interspecific hybrids using morphological and adzukibean specific SSR markers. Abbas et al (2015) used SSR and RAPD markers to confirm the hybridity of interspecific hybrids between moongbean and urdbean.…”
Section: Confirmation Of Hybridity Of Interspecific Hybridssupporting
confidence: 67%
“…Some of the researchers have successfully studied the gene flow from wild to cultivated Vigna, and they have noticed that there is enough opportunity to facilitate gene transfer. The resistant gene of YMD has been successfully incorporated into urdbean [175] and mungbean [176,177]. Likewise, Mathivatahana et al [178] used rice bean as a donor for MYMV-resistance in mungbean.…”
mentioning
confidence: 99%
“…The crosses were attempted by using black gram cultivars as the female parents as success rate was higher in these crosses as reported by Biswas and Dana (1975) The pollen fertility of the parents ranged from 92.88 to 94.25 per cent. Bhanu et al (2017) recorded a pollen fertility of 1.6 to 3.4 per cent for the hybrids obtained from the green gram x rice bean cross. The fertility status of the parents and hybrids are presented in Table 4 and Fig.…”
Section: Female Parentsmentioning
confidence: 97%